Risk Factors Associated with Periodontal Diseases for Patients over 30 years old Attending the Dental Department, Mahosoth Hospital, Vientiane Capital, Lao PDR - THAMMAVONGSA, Viengsay; THAMMAVONGSA, Khambay; PHENTHAVONG, Mamivone; LYVONGSA , Akao; SAMOUNTRY , Bountom; DONPHASID, Viengnaknone; THAMMAVONGSA, Pouthasone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research was a descriptive the risk factors associated with periodontitis diseases for respondents age over 30 years old at Mahosot Hospital, Vientiane Capital, Lao PDR. The aims of this were to: 1) investigate of periodontitis diseases situation and 2) analyse the factors effecting periodontitis diseases with thesample group of 297 respondents and analyzed the data by using the SPSS program. The result found that age between 36-59 years old have got risk periodontitis diseases equal 22.2 %, and 34.4% was pocket depth (PD) morethan 4 mm. The study also found that personal diseasesfactor, behaviour of cleaning mouth or times of brush tooth factor, and go to see the Doctor every year or once a year factor these were related to periodontitis diseases and protect periodontitis diseases with the statistically significant (p-value <0.05).